On the Role of Biogeochemical Coupling Between Sympagic and Pelagic Ecosystem Compartments for Primary and Secondary Production in the Barents Sea - Benkort, Déborah; Daewel, Ute; Heath, Michael; Schrum, Corinna (Frontiers in Environmental Science, 2020)
Primary production in the Arctic marine system is principally due to pelagic phytoplankton. In addition, sea-ice algae also make a contribution and play an important role in food web dynamics. A proper representation of sea-ice algae phenology and the linkage with the pelagic and benthic systems is needed, so as to better understand the ecosystem response to warming and shrinking ice cover. Here we describe the extension of the biogeochemical model ECOSMO II to include a sympagic system in the model formulation, illustrated by implementation in the Barents Sea. The new sympagic system formulation includes four nutrients (NO3, NH4, PO4, and SiO2), one functional group for sea-ice algae and one detritus pool, and exchanges with the surface ocean layer. We investigated the effects of linkage between the three systems (sympagic, pelagic and benthic) on the ecosystem dynamic; the contribution of the ice algae to total primary production; and how the changes in ice coverage will affect the lower trophic level Arctic food-web dynamics. To solve the scientific and technical challenges related to the coupling, the model was implemented in a 1-D application of the General Ocean Turbulence Model (GOTM). Results showed that the model simulated the seasonal pattern of the sympagic components realistically when compared to the current knowledge of the Barents Sea. Our results show that the sympagic system influences the timing and the amplitude of the pelagic primary and secondary production in the water column. We also demonstrated that sea-ice algae production leads to seeding of pelagic diatoms and an enhancement of the zooplankton production. Finally, we used the model to explain how the interaction between zooplankton and ice algae can control the pelagic primary production in the Barents Sea.